Analysis of the hematological profile and the coproparasitological examination of dogs in relation to the indication of the presence of verminosis in a kennel in Porto Velho – RO (Research, Society and Development, 2021)
In many cases, guardians are unaware of the issues of animal health care and do not promote any type of antiparasitic protocol or even perform it inappropriately, which tends to be a zoonotic factor, thus making adequate treatment extremely important. Thus, the fecal stool examination (EPF) together with the evaluation of the blood count, make it possible to diagnose a large number of parasitic diseases. The present study aims to evaluate the results of the hematological and coproparasitological profile in the indicative for verminosis in animals from a kennel in Porto Velho, Rondônia. The work was carried out in a kennel in Porto-Velho, Rondônia, with the collection of blood and feces from dogs of different breeds, age and sex. The hematological examination showed that 12.5% ​​(2/16) of the animals analyzed presented eosinophilia, therefore, 87.5% (14/16) of the group did not exceed the limit of reference values ​​for canines for eosinophils (150 -1,250 eosinophils/µl) used in a veterinary hospital of a higher education institution. The results of the coproparasitological examination indicated that 18.75% (3/16) of the fecal samples had Ancylostoma sp. eggs, therefore, 81.25% (13/16) did not present verminosis. It is concluded that there was a divergence between the methods, in which the coproparasitological examination using the Willis-Mollay technique was evidenced as more reliable in the evaluation of parasitosis, on the other hand, the device for automated hematological examination was not effective, indicating the different results.